Psychological factors influencing child safety awareness: a study on abduction prevention education - Ampofo, Joshua; Bentum-Micah, Geoffrey; Qinggong, Li; Changfeng, Wang; Guoan, Le; Sun, Binghai; Xusheng, Qian (Frontiers in Education, 2025)
BackgroundChild safety awareness is critical, particularly in abduction prevention. This study investigates psychological factors influencing safety awareness in children, recognizing the limitations of primarily informational approaches.MethodsA mixed-methods approach was employed with 300 children aged 6–12 and 30 parents/educators. Quantitative data were collected via surveys measuring self-efficacy, anxiety, and safety awareness. Qualitative data were gathered through semi-structured interviews exploring experiences and perceptions.ResultsQuantitative analyses revealed a significant positive correlation between self-efficacy and safety awareness [r = 0.62, p < 0.001, 95% CI (0.54, 0.70)] and a significant negative correlation between anxiety and safety awareness [r = −0.47, p < 0.001, 95% CI (−0.55, −0.38)]. Qualitatively, key themes included the importance of open communication, the complex impact of parental anxiety (e.g., one parent noted, “I worry I’m scaring him”), and the effectiveness of interactive educational strategies.ConclusionComprehensive education programs should enhance self-efficacy while managing anxiety and promoting open communication. This research integrates psychological insights to inform future interventions to improve child protection strategies.